2008
DOI: 10.1071/py08010
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Observations on Vietnamese Children's Oral Health Practices and Use of the Child Oral Health Services in Central Sydney: A Qualitative Study

Abstract: The research was conducted to describe Vietnamese-speaking parents' practices in children's oral health care and to identify barriers parents had in accessing child dental services after being notified that their child needed treatment. A qualitative study design was employed, using a stratified purposive sample of five focus groups and three semi-structured interviews. A multidisciplinary team conducted a thematic analysis on the translated transcripts of the focus groups and interview notes. The retention of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In addition to the lack of awareness of preventative dental health, the study parents cited language difficulties as being a major barrier to accessing school-based oral health programs for their children [13].…”
Section: Utilisation Of Health Servicesmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition to the lack of awareness of preventative dental health, the study parents cited language difficulties as being a major barrier to accessing school-based oral health programs for their children [13].…”
Section: Utilisation Of Health Servicesmentioning
confidence: 99%
“…A study into Vietnamese-born parents' oral health practices [13] concluded that Vietnamese parents in Australia retain traditional oral health practices and utilised oral health and dental services only when symptoms arose (e.g., toothache), rather than in a preventative manner. In addition to the lack of awareness of preventative dental health, the study parents cited language difficulties as being a major barrier to accessing school-based oral health programs for their children [13].…”
Section: Utilisation Of Health Servicesmentioning
confidence: 99%
See 2 more Smart Citations